The Effect of Bima Traditional Baby Massage on Sleep Pattern among Infants aged 5-12 Months - Kurniadi, Kurniadi (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2020)
Background: Massage was a tactile stimulation that has physiological and biochemical effects in the body. Baby massage was a fun way to relieve tension and anxiety, especially in infants. Gentle massage will help relax the muscles so that the baby becomes calm and sleeps soundly. Good quality sleep can achieve optimal growth and development. The purpose of this study was to determine the effect of pe'e culture (baby massage) on the sleep needs of babies aged 5-12 months.Subjects and Method: This research was a quasi-experimental study with a pre and post test design in the same group. The number of samples in this study were 30 respondents using purposive sampling technique. The dependent variable of this study was sleep resting children aged 5-12 months. The independent variable was Bima traditional massage (pe'e). Data analysis was performed using the Wilcoxon test.Results: Average sleep quality of children aged 5-12 months after treatment (Mean= 2.73; SD= 6.40) is higher than before treatment (Mean= 1.47; SD= 5.07), and statistically significant (p= <0.001).Conclusion: Culture Baby massage (pee) can improve sleep rest patterns in infants aged 5-12 months.Keywords: baby massage, sleep patterns, sleep quality, age 5-12 monthsCorrespondence: Kurniadi. Health Polytechnics, Ministry of Health, Mataram, Lombok, West Nusa Tenggara. Email: kurniadi.poltekkes@gmail.comIndonesian Journal of Medicine (2020), 05(02): 142-147https://doi.org/10.26911/theijmed.2020.05.02.08